Comparison of recovery profiles of propofol and sevoflurane anesthesia with bispectral index monitoring in percutaneous nephrolithotomy - Orhon, Zeynep Nur (The Korean Society of Anesthesiologists, 2013)
BACKGROUND: The aim of the study was to evaluate the comparative effects of propofol infusion versus sevoflurane for maintenance of anesthesia with respect to hemodynamics, recovery characteristics, nausea and vomiting in patients undergoing percutaneous nephrolithotomy. METHODS: Forty American Society of Anesthesiologists physical status I-II patients, aged between 22 and 65 years were randomly divided to receive either intravenous anesthesia with propofol (group P) or sevoflurane (group S). Cardiovascular variables, peripheral oxygen saturation (SpO(2)), end-tidal carbon dioxide (ETCO(2)), bispectral index (BIS) and train-of-four (TOF) values were recorded at intervals throughout the procedure. Time to spontaneous respiration, eye opening, extubation, obey commands, hand squeezing, Aldrete Score > 9 and the incidence of postoperative nausea and vomiting were recorded. RESULTS: Early recovery times [spontaneous respiration (P = 0.002), eye opening (P = 0.006), extubation (P = 0.013), obey commands (P < 0.05), hand squeezing (P = 0.005)] were significantly longer in group P. The incidence of vomiting was significantly higher in group S (P < 0.05). Hemodynamic parameters, levels of SpO(2), ETCO(2), and BIS and TOF values were not significantly different between the groups (P > 0.05). CONCLUSIONS: The present study which adjusted sevoflurane concentration and propofol infusion rate according to BIS values revealed that maintenance of anesthesia with sevoflurane is associated with faster recovery than anesthesia with propofol. Propofol resulted in a significantly lower incidence of postoperative nausea and vomiting. Hemodynamic parameters and levels of SpO(2) and ETCO(2) were comparable between the groups during percutaneous nephrolithotomy.